FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT PERBANKAN (Studi pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode 2010-2012) (Students' Journal of Accounting and Banking, 2014)
This study aims to analyze the factors that effect bank credit, which includes the Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and Return on Assets (ROA).The population used in this research are banking companies listed on the Indonesian Stock Exchange 2010-2012. And to importance the research used samples with the method of“purposive sampling”, so the result is 28 banks that met the criteria. The method used in this research is multiple regression analysis. Based onthe results of the partial test banks listed on the Indonesian Stock Exchange indicates that the variable TPF have positive and significant effect to the credit. While the variable CAR have negative and insignificant to the credit.Variable NPL and ROA have positive and insignificant effect to the credit.Keywords: Credit, Third Party Funds (TPF), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Return On Assets (ROA)